A Hydrogen‐Bonded yet Hydrophobic Porous Molecular Crystal for Molecular‐Sieving‐like Separation of Butane and Isobutane. Issue 51 (7th October 2020) - Ye, Zi‐Ming; Zhang, Xue‐Wen; Liao, Pei‐Qin; Xie, Yi; Xu, Yan‐Tong; Zhang, Xue‐Feng; Wang, Chao; Liu, De‐Xuan; Huang, Ning‐Yu; Qiu, Ze‐Hao; Zhou, Dong‐Dong; He, Chun‐Ting; et al.
Abstract: Porous molecular crystals sustained by hydrogen bonds and/or weaker connections are an intriguing type of adsorbents, but they rarely demonstrate efficient adsorptive separation because of poor structural robustness and tailorability. Herein, we report a porous molecular crystal based on hydrogen‐bonded cyclic dinuclear Ag I complex, which exhibits exceptional hydrophobicity with a water contact angle of 134°, and high chemical stability in water at pH 2–13. The seemingly rigid adsorbent shows a pore‐opening or nonporous‐to‐porous type butane adsorption isotherm and complete exclusion of isobutane, indicating potential molecular sieving. Quantitative column breakthrough experiments show slight co‐adsorption of isobutane with an experimental butane/isobutane selectivity of 23, and isobutane can be purified more efficiently than for butane. In situ powder/single‐crystal X‐ray diffraction and computational simulations reveal that a trivial guest‐induced structural transformation plays a critical role. Abstract : A rigid hydrogen‐bonded porous molecular crystal shows not only exceptionally high hydrophobicity and chemical stability, but also molecular‐sieving‐like separation of butane/isobutane associated with a trivial guest‐induced structural transformation revealed by powder/single‐crystal X‐ray diffraction and computational simulations.